Combining eDNA metabarcoding and conventional method in rapid screening of fish diversity in Maros-Pangkep Global Geopark, South Sulawesi, Indonesia - AMBENG AMBENG; MUHAMMAD IQRAM; MAGDALENA LITAAY; ZOHRAH HASYIM; WILMA J. C. MOKA; GEORGINA MARIA TINUNGKI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ambeng, Iqram M, Litaay M, Hasyim Z, Moka WJC, Tinungki GM. 2024. Combining eDNA metabarcoding and conventional method in rapid screening of fish diversity in Maros-Pangkep Global Geopark, South Sulawesi, Indonesia. Biodiversitas 25: 819-828. A newly designated geopark by UNESCO, Maros-Pangkep Global Geopark, South Sulawesi, Indonesia owns great geodiversity, exceptional cultural heritage, and high biodiversity. However, the global biodiversity crisis that has hit the earth might also occur in Maros-Pangkep river systems, potentially threatening endemic freshwater fish and all other biota. It has been reported that there is high pressure on the environment along the watershed in the Maros-Pangkep rivers, including a high sedimentation rate downstream, which is linked to extreme erosion upstream and could eventually affect fish populations such as endemic ones. This should prompt a call for the authorities to build a strategy for monitoring and documenting aquatic biota such as fish to preserve biodiversity. Environmental DNA (eDNA) could be considered a method for monitoring fish species based on the DNA traces they shed in the water. Hence, this study aims to use eDNA to survey fish biodiversity in several rivers in the Maros-Pangkep Global Geopark and compare the result against the traditional gillnet method. The results showed that using two methods, 29 fish species in 19 families and 15 orders were obtained from the three rivers. Despite the majority of detected species, 25 species, as the result of using eDNA, 4 species were only detected using a traditional method which eDNA failed to identify. Among those species, several endemic and non-native species were successfully identified by either one or both methods. This could eventually be a suggestion for responsible authorities in biodiversity conservation to combine both approaches to monitor and conserve local biodiversity.